Function of a Sermon: Dutch-American Reformed and Manado Adventism Tradition - Iwan Simbolon; Bartolomeus D. Nainggolan; Milton T. Pardosi (Peneliti.net, 2023)
A sermon is an essential part in church liturgical, where the church’s core message transformed to its congregation. Indeed, every church tradition share distinct expression on sermon functions. Therefore, by a comparison study, constructive contributions are possible to be delved. This article attempts to explore function of a sermon in Dutch-American Reformed and Manado Adventism tradition. By using qualitative approach, this essay encompasses articles, books, and any related resources that could rich the description. In sum, both traditions agree that a sermon is a media to extend dogmatic and encourage preacher to present expected performance. Further, Dutch-American tradition stands to the importance of repenting and significant sequence of each Christianity experience while Manado Adventism considers a sermon as the media of doctrinal transfer.